2012
DOI: 10.1021/la301587f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Patterning of Nanoparticles and Polymers Using an Evaporation Driven Flow in a Vapor Permeable Template

Abstract: Nanoparticles and polymers have great potential for lowering cost and increasing functionality of printed sensors and electronics. However, creation of practical devices requires that many of these materials be patterned on a single substrate, and many current patterning processes can only handle a single material at a time, necessitating alignment of serial processing steps. Higher throughput and lower cost can be achieved by patterning multiple materials simultaneously. To this end, the microfluidic molding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…To solve the abovementioned problems, several solvent-permeable molds have been previously reported. [15][16][17][18][19][20] In our studies on the design of lithography materials derived from biomass, solvent-permeable molds www.advancedsciencenews.com www.mme-journal.de peeling induced by demolding during the nanoimprint lithography processes. The adhesion underlayer material of novolac derivatives has been developed and reported.…”
Section: Methodsmentioning
confidence: 99%
“…To solve the abovementioned problems, several solvent-permeable molds have been previously reported. [15][16][17][18][19][20] In our studies on the design of lithography materials derived from biomass, solvent-permeable molds www.advancedsciencenews.com www.mme-journal.de peeling induced by demolding during the nanoimprint lithography processes. The adhesion underlayer material of novolac derivatives has been developed and reported.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, we investigated in depth these mechanisms, mainly for aqueous dispersions of nanoparticles 23 and demonstrated successful fabrications of nanoparticle-dense assemblies, with applications ranging from optical metamaterials 24 to surface-enhanced Raman spectroscopy substrates 25 . Demko et al 26,27 also reported similar works and extended the pervaporation technique to the use of non-aqueous dispersions, using the development of a solvent-compatible permeable matrix.
Fig. 1Fabrication process flow of multilayer polymer micro-structures. a (Left) Reversible sealing of dead-end channels embedded in a PDMS mold by a PDMS membrane.
…”
Section: Introductionmentioning
confidence: 92%
“…These phenomena result from a subtle coupling between the build-up of mechanical stresses during solidification, mechanical deformations of the PDMS matrix, and adhesion between the composite and the PDMS walls. Demko et al 26,27 showed that the use of a more rigid, but still permeable, matrix allows to minimize such deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Permeable templates of gases and solvents have also been reported to solve air trapping and template damage caused by gases such as nitrogen and oxygen generated from microimprinted materials . Volatile solvents produced from the formulation of such materials, as well as gases such as nitrogen and oxygen generated from them that are involved in the cross‐linked reactions, cause incomplete filling of the cross‐linked liquid materials in the template during the UV or thermal curing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Permeable templates of gases and solvents have also been reported to solve air trapping and template damage caused by gases such as nitrogen and oxygen generated from microimprinted materials. [7][8][9][10] Volatile solvents produced from the formulation of such materials, as well as gases such as nitrogen and oxygen generated from them that are involved in the cross-linked reactions, cause incomplete fi lling of the cross-linked liquid materials in the template during the UV or thermal curing processes. The use of volatile solvents with high coating property and solubility into the microimprinted materials, such as the conventionally used compounds, plastic resins, and imprinted materials, has been limited in mold injection and imprint lithography.…”
Section: Introductionmentioning
confidence: 99%